Virtual Prototyping of the 5-Axis Hybrid Robot for Milling - Michał MANKA; Grzegorz KARPIEL; Maciej PETKO; Janusz OCHONSKI; Konrad GAC And Grzegorz GORA (Communications of International Proceedings, 2024)
The paper presents the virtual prototyping of a parallel manipulator for milling. Using parallel manipulators as a numerically controlled milling machine has many advantages. However, due to their specificity, they require advanced control algorithms that must be tuned before they are implemented on a physical device. The process of tuning the control system can be carried out by using virtual prototyping, especially by co-simulation of the control system model and the dynamic model of the device, which is presented in this article.
Keywords: SIMULATION; DYNAMIC MODELLING; CO-SIMULATION; PARALLEL ROBOTS; CNC MACHINE